Analysis of the Effect of Net Income, Total Assets and Total Cash Flow on the Stock Price of Companies Indexed LQ45 - Mareza, Puja Dwi; Handajani, Lilik; Kartikasari, Nungki (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The Indonesian capital market has experienced rapid growth, marked by an increase in the number of investors and companies listed on the Indonesia Stock Exchange (IDX). The LQ45 Index, which includes companies with high liquidity and large market capitalization, serves as a key indicator of the capital market. This study aims to analyze the effect of net profit, total assets, and cash flow on the stock prices of companies included in the LQ45 Index during the 2020–2022 period. A quantitative method with an associative approach was employed to evaluate the relationships between variables, using data from the annual financial reports of 58 companies selected through purposive sampling. Data analysis was conducted using IBM SPSS 25, with classical assumption tests, F-tests, and t-tests applied to test the hypotheses. The results indicate that, simultaneously, net profit, total assets, and total cash flow significantly influence stock prices. However, partially, net profit does not have a significant impact on stock prices, suggesting that this factor is less considered by investors. In contrast, total assets and total cash flow significantly affect stock prices, emphasizing the importance of asset management and corporate liquidity. These findings suggest that companies should focus on effective asset and cash flow management to attract investors and enhance financial report transparency. Future research may consider additional variables and extend the study period.